2016
DOI: 10.1093/mnras/stw632
|View full text |Cite
|
Sign up to set email alerts
|

Hot and turbulent gas in clusters

Abstract: The gas in galaxy clusters is heated by shock compression through accretion (outer shocks) and mergers (inner shocks). These processes additionally produce turbulence. To analyse the relation between the thermal and turbulent energies of the gas under the influence of non-adiabatic processes, we performed numerical simulations of cosmic structure formation in a box of 152 Mpc comoving size with radiative cooling, UV background, and a subgrid scale model for numerically unresolved turbulence. By smoothing the g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 61 publications
6
60
0
Order By: Relevance
“…Also, we justified using the Smagorinsky model by assuming that the local equilibrium condition holds, where the kinetic energy transfer rate down the turbulent cascade is equal on all scales. While the assumption is approximately true on average in the regimes we investigated (Schmidt et al 2016), a fully-consistent turbulence model involves tracking the sub-grid kinetic energy via an additional transport equation that includes all of the necessary, higher-order, sub-grid scale terms (Schmidt 2015). However, the dynamic model mitigates the issue by inherently calculating the deviations from local equilibrium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we justified using the Smagorinsky model by assuming that the local equilibrium condition holds, where the kinetic energy transfer rate down the turbulent cascade is equal on all scales. While the assumption is approximately true on average in the regimes we investigated (Schmidt et al 2016), a fully-consistent turbulence model involves tracking the sub-grid kinetic energy via an additional transport equation that includes all of the necessary, higher-order, sub-grid scale terms (Schmidt 2015). However, the dynamic model mitigates the issue by inherently calculating the deviations from local equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…In order for this to be possible, the local equilibrium condition must be approximately true in the regime of interest. We are specifically interested in cosmological-scale gas, and Schmidt et al (2016) show that the local equilibrium condition holds -on average -in a cosmological-scale volume. Introducing the dynamic model on top of these approximations further supports our model assumption, because the dynamic model inherently accounts for the deviations from local equilibrium.…”
Section: Diffusivitymentioning
confidence: 99%
“…However, compressible turbulence in astrophysical systems is often found in the intermediate regime (q ∼ w). An important example is the intracluster medium in clusters of galaxies [41,42]. is publicly available on Github.…”
Section: Discussionmentioning
confidence: 99%
“…Global refinement by overdensity and vorticity made the simulations extremely resource-intensive, limiting their resolution to 78 kpc. To improve on that and to increase the mass resolution at least for a selected cluster, we centred the box at the density peak of the most massive halo (halo 1 in Table 4 in Schmidt et al 2016; the halo mass is M halo = 6.68 × 10 14 M , its maximal radial extent R halo = 3.24 Mpc, and R500 = 1.04 Mpc). Further analysis revealed that this cluster is the result of a major merger at low redshift.…”
Section: Numerical Methods and Modelsmentioning
confidence: 99%
“…In this article, we revisit the problem of major mergers of cool-core clusters from the perspective of dynamical processes in numerical simulations. We consider the limiting case of gas dynamics with radiative cooling and a homogeneous UV background based on the simulations reported in Schmidt et al (2016), as summarised in the next section. Since no local feedback is applied, gravitational heating, shock compression, and turbulent dissipation are the major sources of thermal energy.…”
Section: Introductionmentioning
confidence: 99%